2013
DOI: 10.1002/masy.201300101
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tissue Adhesives Based on Amphiphilic Isocyanate‐Terminated Trimethylene Carbonate Block Copolymers

Abstract: Summary: In this study, novel 3-armed star-shaped isocyanate-terminated block copolymers based on trimethylolpropane ethoxylate (TMPE) and trimethylene carbonate (TMC) varying in composition were designed and synthesized. By reaction with water, networks were formed. The characteristics of these networks were compared with those prepared from analogous linear structures based on polyethylene glycol (PEG) and TMC. Tensile testing of the networks highlighted good mechanical properties. In lap shear adhesion test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Analysis by 1 H-NMR after each synthesis step and FTIR confirmed that the adhesive hyper-branched block copolymers were successfully synthesized [12, 13]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis by 1 H-NMR after each synthesis step and FTIR confirmed that the adhesive hyper-branched block copolymers were successfully synthesized [12, 13]. …”
Section: Resultsmentioning
confidence: 99%
“…The cross-linking component was a mixture of spermidine (Sigma Aldrich, the Netherlands) and a linear copolymer HO-TMC 2 -PEG 400 -TMC 2 -OH, which was prepared as described previously [12]. Spermidine was chosen as a natural low molecular weight polyamine with low viscosity, which enabled easy mixing with other components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] The building blocks of the copolymer were trimethylolpropane ethoxylate (TMPE, M n = 450 g/mol), trimethylene carbonate (TMC), and hexamethylene diisocyanate (HDI).…”
Section: Experimental Tissue Adhesivesmentioning
confidence: 99%
“…We recently reported on the development of reactive three-armed and hyper-branched block copolymeric tissue adhesives that can attach to the tissue via covalent bonding [17, 18] In a following study, meniscus explants were glued with these adhesives and cultured in vitro. It was shown that both developed materials have satisfactory bonding strengths to the tissue and did not exhibit toxicity to the cells, and therefore have the potential to be used in the treatment meniscal tears (unpublished work).…”
Section: Introductionmentioning
confidence: 99%